ENHANCING WORKPLACE PERFORMANCE IN PRIVATE MEDICAL COLLEGES THROUGH STAFF TRAINING: A SYSTEMATIC LITERATURE REVIEW - Hayat, Salma; Wahab, Siti Norida; Othman, Norashida; Ahmad, Muhammad (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This research critically evaluates whether staff training in private medical colleges enhances workplace performance, focusing on effective training techniques and challenges. By adopting a systematic literature review that appraises and synthesizes previous studies to investigates the role of various training techniques in enhancing workplace performance, identifying effective practices, challenges, and areas required for further improvements. Through the PRISMA approach, 24 research articles were systematically selected, and published from 2016 to 2024 in Web of Science, ScienceDirect, PubMed, Researchgate, IEEE, and Google Scholar. Proper screening of studies has been performed for further consideration from an initial list of 648 articles. This finding indicates integrated workshops, soft skills training, and experiential learning boost staff capabilities, job satisfaction, and workplace performance. It also reveals the importance of training needs for stakeholders, emphasizing a structured training framework while its conclusions are restricted by secondary data and geographical limitations of existing research. This study focused on staff training techniques and associated challenges but analysis may not be applicable for digital training, which has become a fundamental aspect of modern workplace learning. Excluding articles published before 2016, the finding may introduce limitations in the accuracy of the result. Existing literature mostly focuses on a single aspect of training either soft skills or technical (hard skills) training without combining all these aspects into one framework. The study also assists existing literature on staff training and workplace performance in private medical colleges.